2013
DOI: 10.1038/msb.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification of proteins that elicit drug side effects

Abstract: Protein–side effects associations are identified by integrating drug–target data with side effects information from drug labels. Benchmarking against the literature and validation with an in vivo mouse model shows that these pairs correspond to causal relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
150
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(162 citation statements)
references
References 41 publications
(67 reference statements)
7
150
0
Order By: Relevance
“…As SIDER2 consists of recognized side effects only, we cannot reliably distinguish between false positive signals and previously unknown ADRs. Furthermore, SIDER was compiled from package insert information by NLP tools [79], and as such may include side effects that seldom occur in practice or false associations that were caused by text-mining errors [150]. While SIDER2 is sufficient to evaluate the hypotheses of the current work, in future work we plan to incorporate other data sources, such as EHR data and FDA reports.…”
Section: Discussionmentioning
confidence: 99%
“…As SIDER2 consists of recognized side effects only, we cannot reliably distinguish between false positive signals and previously unknown ADRs. Furthermore, SIDER was compiled from package insert information by NLP tools [79], and as such may include side effects that seldom occur in practice or false associations that were caused by text-mining errors [150]. While SIDER2 is sufficient to evaluate the hypotheses of the current work, in future work we plan to incorporate other data sources, such as EHR data and FDA reports.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the side effects of the drugs, we considered SIDER2 (http://sideeffects.embl.de/, last accessed October 10, 2014) database (Kuhn et al 2013). Thereby, we compiled a list of 996 drugs associated with 4,192 side effects.…”
Section: Methodsmentioning
confidence: 99%
“…Second, many associations go undiscovered in cases of a small number of drugs interacting with a particular protein (e.g. fewer than five drugs per target as mentioned in some publications) [53]. Therefore, estimated profiles are relatively small (few hundred targets) and include mostly therapeutic drug targets as well as metabolizing enzymes and transporters, but only a few off-target proteins.…”
Section: Drug Targets and Pathwaysmentioning
confidence: 98%
“…As an example, Kuhn et al performed a large-scale search for potential ADR-protein associations and found corresponding direct and ://www.informatics.jax.org/) for most of the identified associations[53]. If there is no directinformation in the literature, the functions of revealed proteins can be compared to the functions of proteins with known associations to the corresponding disease.…”
mentioning
confidence: 98%